Climate change and marine and freshwater toxins - Aditee, Mitra; Bouwman, A. F.; Anas, Ghadouani; Anke, Kremp; Arthur H. W., Beusen; Begoña, Espiña; Botana, Luis M.; Madden, Christopher J.; Cynthia A., Heil; Dani J., Barrington; Elke S., Reichwaldt; Fan, Zhang; et al. (Walter de Gruyter, 2021)
The increasingly widespread production of toxins by marine and freshwater microalgae raises serious concerns regarding seafood and drinking water safety. This book compiles studies on the influence of climate change on the spreading of toxin-producing species in aquatic systems. The chemistry and biology of toxin production is revised and an outlook on control and prevention of the toxins' impact on human and animal health is given.